Diagnostic challenges with accurate identification of Listeria monocytogenes isolates from food and environmental samples in South Africa - Teena S.M. Thomas; Juno Thomas; Karren le Roux; Sanelisiwe T. Duze; Faith Mkhwanazi; Adriano Duse (AOSIS, 2022)
Background: The 2017-2018 listeriosis outbreak in South Africa warranted testing for Listeria monocytogenes in food products and processing environments. Diagnostic tests are needed to accurately differentiate L. monocytogenes from other Listeria species. Objective: The study assessed the performance of the commonly used tests in our setting to accurately identify L. monocytogenes. Methods: The study was conducted in a public health laboratory in South Africa. Cultured isolates from food and environmental samples were tested both prospectively and retrospectively between August 2018 and December 2018. Isolates were phenotypically identified using tests for detecting β-haemolysis, Christie-Atkins-Munch-Peterson, alanine arylamidase (AlaA), mannosidase, and xylose fermentation. Listeria monocytogenes isolates were identified using automated systems, Microscan Walkaway Plus 96, Vitek® MS, Vitek® 2 and Surefast Listeria monocytogenes PLUS PCR. All results were compared to whole-genome sequencing results. Results: β-haemolysis and Christie-Atkins-Munch-Peterson tests gave delayed positivity or were negative for L. monocytogenes and falsely positive for one strain of Listeria innocua. The AlaA enzyme and Colorex Listeria agar lacked specificity for L. monocytogenes identification. Based on a few phenotypic test results, an aberrant L. monocytogenes strain and Listeria seeligeri strain were reported. All automated platforms overcalled L. monocytogenes in place of other Listeria species. Conclusion: No test was ideal in differentiating Listeria species. This is an issue in resource-limited settings where these tests are currently used. Newer technologies based on enzyme-linked immunosorbent assay and other molecular techniques specific to L. monocytogenes detection need to be investigated.